2021
DOI: 10.1155/2021/2629150
|View full text |Cite
|
Sign up to set email alerts
|

Transneuronal Degeneration in the Visual Pathway of Rats following Acute Retinal Ischemia/Reperfusion

Abstract: The maintenance of visual function not only requires the normal structure and function of neurons but also depends on the effective signal propagation of synapses in visual pathways. Synapses emerge alterations of plasticity in the early stages of neuronal damage and affect signal transmission, which leads to transneuronal degeneration. In the present study, rat model of acute retinal ischemia/reperfusion (RI/R) was established to observe the morphological changes of neuronal soma and synapses in the inner ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Retinal ischaemia/reperfusion (I/R) is a common pathological feature of these diseases, but effective targeted treatments are currently lacking [ 3 , 4 ]. Researchers have found that interventions targeting RGC death cannot restore visual function [ 5 ]. Therefore, other vital factors may contribute to visual dysfunction after I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ischaemia/reperfusion (I/R) is a common pathological feature of these diseases, but effective targeted treatments are currently lacking [ 3 , 4 ]. Researchers have found that interventions targeting RGC death cannot restore visual function [ 5 ]. Therefore, other vital factors may contribute to visual dysfunction after I/R injury.…”
Section: Introductionmentioning
confidence: 99%